In-situ MnO2 Electrodeposition and its Negative Impact to Rechargeable Zinc Manganese Dioxide Batteries - Liang, Rui Lin (University of Waterloo, 2018)
Achieving high rechargeability with the economically feasible and environmentally friendly Zn-MnO2 batteries has been the goal of many scientists in the past half century. Recently, the stability of the system saw a significant improvement through adaptation of mildly acidic electrolyte with Mn2+ additives that prevent dissolution of the active cathode materials, MnO2. With the new design strategy, breakthroughs were made with the battery life span, as the lab scale batteries operated with minimal degradation for over a thousand cycles of charge and discharge at high C-rate ( >5C ) cycling. However, low C-rate operation of these batteries is still limited to 100 cycles, but has not been a focal point of the research efforts. Furthermore, the electrochemical reactions within the battery system are still under debate and many questions remain to be answered. An interesting phenomenon investigated in this thesis about the mildly acidic Zn-MnO2 battery systems is their tendency to experience capacity growth caused by formation of new active material through Mn2+ electrodeposition. The deposition reaction is thermodynamic favored within the battery operating voltage window and is considered by some as beneficial for battery performance. This general belief is challenged by the investigations and experimentations in this thesis, as results indicate the MnO2 polymorph generated are not ideal for long term cycling and would eventually lead to formation of electrochemically inactive Mn species. Uncontrolled, continuous occurrence of the reaction would also leads to Mn2+ ion depletion and uplifting of the protection they provide. The electrodeposition is therefore relabelled as a gateway that allows undesired reaction to occurred within Zn-MnO2 batteries; a long term crystal transaction mechanism of the active cathode material was also formulated based on the post cycling characterizations of the electrodes. With the newly developed recognition of the battery stability issues, a design strategy focused on suppressing MnO2 electrodeposition through manipulating the reaction kinetic is proposed. The effectiveness of the strategy was showcased by cathode electrodes incorporated with expanded graphite, a hydrophobic substrate material discovered to be non-ideal for MnO2 electrodeposition. The resulting polymer-free III electrode exhibit much improved low C-rate cycling stability of over 300 cycles with minimal capacity decay and rate performances that are comparable to state-of-the-art Zn-MnO2 battery cathode electrodes. These significant electrochemical performance improvements validate the effectiveness of the strategy, and it is intended to be a key concept that would serve as an important stepping stone for further optimization of the Zn-MnO2 battery system.
Keywords: rechargeable Zn-MnO2 batteries; Storage batteries; Electroforming